Pyrroline-5-Carboxylate Reductase 1 Directs the Cartilage Protective and Regenerative Potential of Murphy Roths Large Mouse Mesenchymal Stem Cells - Tejedor, Gautier; Contreras-Lopez, Rafael; Barthelaix, Audrey; Ruiz, Maxime; Noël, Danièle; De Ceuninck, Frédéric; Pastoureau, Philippe; Luz-Crawford, Patricia; Jorgensen, Christian; Djouad, Farida (Frontiers in Cell and Developmental Biology, 2021)
Murphy Roths Large (MRL) mice possess outstanding capacity to regenerate several tissues. In the present study, we investigated whether this regenerative potential could be associated with the intrinsic particularities possessed by their mesenchymal stem cells (MSCs). We demonstrated that MSCs derived from MRL mice (MRL MSCs) display a superior chondrogenic potential than do C57BL/6 MSC (BL6 MSCs). This higher chondrogenic potential of MRL MSCs was associated with a higher expression level of pyrroline-5-carboxylate reductase 1 (PYCR1), an enzyme that catalyzes the biosynthesis of proline, in MRL MSCs compared with BL6 MSCs. The knockdown of PYCR1 in MRL MSCs, using a specific small interfering RNA (siRNA), abolishes their chondrogenic potential. Moreover, we showed that PYCR1 silencing in MRL MSCs induced a metabolic switch from glycolysis to oxidative phosphorylation. In two in vitro chondrocyte models that reproduce the main features of osteoarthritis (OA) chondrocytes including a downregulation of chondrocyte markers, a significant decrease of PYCR1 was observed. A downregulation of chondrocyte markers was also observed by silencing PYCR1 in freshly isolated healthy chondrocytes. Regarding MSC chondroprotective properties on chondrocytes with OA features, we showed that MSCs silenced for PYCR1 failed to protect chondrocytes from a reduced expression of anabolic markers, while MSCs overexpressing PYCR1 exhibited an increased chondroprotective potential. Finally, using the ear punch model, we demonstrated that MRL MSCs induced a regenerative response in non-regenerating BL6 mice, while BL6 and MRL MSCs deficient for PYCR1 did not. In conclusion, our results provide evidence that MRL mouse regenerative potential is, in part, attributed to its MSCs that exhibit higher PYCR1-dependent glycolytic potential, differentiation capacities, chondroprotective abilities, and regenerative potential than BL6 MSCs.